Effect of plant extracts on the techno-functional properties of biodegradable packaging films. (October 2018) - Mir, Shabir Ahmad; Dar, B.N.; Wani, Ali Abas; Shah, Manzoor Ahmad
Abstract: Background: One of the innovations in food packaging includes the development of biodegradable films based on wide range of ingredients. The utilization of these ingredients affects the properties of developed packaging films. Scope and approach: This review provides the recent insights on the effect of plant extracts on the techno-functional properties of biodegradable films including physical, mechanical, barrier, functional, antioxidant and antimicrobial properties. The incorporation of plant extracts into films is a promising method to prevent or reduce the deterioration of food quality, thus contributing to preserving and extending the shelf life of food. Key findings and conclusions: Recent investigations emphasis on the identification of extracts from various plant sources such as leaves, fruits, pomace, seeds, etc. for use in biodegradable polymers. Plant extracts represent an interesting ingredient for biodegradable food packaging material, mainly due to their natural origin and phytochemical properties, allowing for obtaining active materials aiming to extend shelf life and value to the product. This innovative food packaging concept has gaining interest among researchers due to its potential to provide food quality and safety measures. However, their inclusion in biodegradable films for food packaging may imply some impact on properties. Highlights: Plant extracts are used as an active ingredient in biodegradable packaging films. Plant extracts affect the techno-functional properties of biodegradable packaging films. Biodegradable films with plant extracts possess antimicrobial properties.